Pengaruh Harga Dan Lokasi Terhadap Keputusan Pembelian Konsumen Di Pajus (Pajak Usu) Medan - Anggresia, Feni; Siagian, Nalom; Sinaga, Kepler (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This research aims to analyze the influence of price and location on consumer purchasing decisions at USU Tax, one of the traditional markets in Medan with a strategic location and competitive prices. The research method used is quantitative with a non-probability sampling technique. Data analysis was carried out using multiple linear regression using SPSS. The research results show that price and location significantly influence purchasing decisions, this is shown in the results of the partial test (t test) t value (The coefficient of determination (R2) was obtained at 0.818, meaning that the Purchase Decision variable can be explained by the Price and Location variables 81.8% and the remaining 18.2% is influenced by other variables outside the variables of this research. The conclusion in this research is that price and location have a positive and significant effect on consumer purchasing decisions in Pajus.